2015
DOI: 10.1186/s13012-016-0437-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the use of the Consolidated Framework for Implementation Research

Abstract: BackgroundIn 2009, Damschroder et al. developed the Consolidated Framework for Implementation Research (CFIR), which provides a comprehensive listing of constructs thought to influence implementation. This systematic review assesses the extent to which the CFIR’s use in implementation research fulfills goals set forth by Damschroder et al. in terms of breadth of use, depth of application, and contribution to implementation research.MethodsWe searched Scopus and Web of Science for publications that cited the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
885
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 938 publications
(915 citation statements)
references
References 44 publications
14
885
0
16
Order By: Relevance
“…While the CFIR team found no significant alterations to their framework were required (Kirk, Kelley, Yankey, Birken, Abadie, & Damschroder, 2016), we identified a number of important areas for enhancing the CFIR constructs, particularly for community-based agencies interested in a planned and sustainable approach to implementing the best available evidence. These areas include attention to a broad range of stakeholders, including youth and families who are directly impacted by the EIP, several distinct areas that need to be monitored and evaluated (e.g., fidelity to the practice, implementation capacity, process of implementing, client outcomes), and the processes relating to sustaining and spreading the EIP.…”
Section: Discussionmentioning
confidence: 99%
“…While the CFIR team found no significant alterations to their framework were required (Kirk, Kelley, Yankey, Birken, Abadie, & Damschroder, 2016), we identified a number of important areas for enhancing the CFIR constructs, particularly for community-based agencies interested in a planned and sustainable approach to implementing the best available evidence. These areas include attention to a broad range of stakeholders, including youth and families who are directly impacted by the EIP, several distinct areas that need to be monitored and evaluated (e.g., fidelity to the practice, implementation capacity, process of implementing, client outcomes), and the processes relating to sustaining and spreading the EIP.…”
Section: Discussionmentioning
confidence: 99%
“…19 The CFIR synthesized relevant theories into an integrated framework for implementation research and has been widely applied for implementation science. 20 We selected four domains from the adapted CFIR as most relevant to the survey: (1) intervention characteristics (e.g., of the quality measurement program), (2) organizational characteristics; (3) characteristics and roles of providers, and (4) process of implementation. Each domain includes multiple constructs.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to many previous studies, our reporting on selected salient constructs demonstrates CFIR's flexibility and versatility, yet also its limitation in allowing cross-study comparisons where different constructs are reported. Furthermore, we used the CFIR at the post-implementation phase to guide analysis only [34], like most published studies applying the model. Integration and assessment of CFIR throughout the implementation process -from intervention design to outcome analysis -may have produced a more representative picture of implementation characteristics, particularly if specific constructs were more relevant or easily measured at earlier stages.…”
Section: Discussionmentioning
confidence: 99%